ANDRES BELLO AND THE CHALLENGES OF SPANISH AMERICAN LIBERALISM. (24th October 2014) - Dunkerley, James
ABSTRACT: Andrés Bello (1781–1865) is generally reckoned to be the foremost intellectual amongst opponents of the Spanish empire in the Americas after the Napoleonic Wars. This paper provides a synoptic account of Bello's development as a scholar, politician and statesman from his early career as a servant of the crown in colonial Caracas, through his nineteen-year exile in London, to his prominent role in the institutional design and management of the young Chilean republic. The paper traces the historiographical treatment of Bello and the application of his cosmopolitan learning to the tasks of nineteenth-century state-building. It is suggested that his trajectory reflected a successful adaptation of liberal precepts to a conservative local social setting within a world order dominated by British promotion of free trade.